Reindeer Husbandry Adaptation to the Changing Arctic, Volume 1 - Mathiesen, Svein Disch; Eira, Inger Marie Gaup; Turi, Ellen Inga; Oskal, Anders; Pogodaev, Mikhail; Tonkopeeva, Marina (Springer Polar Sciences,, 2023)
This open access book focuses on climate change, Indigenous reindeer husbandry, and the underlying concept of connecting the traditional knowledge of Indigenous reindeer herders in the Arctic with the latest research findings of the world's leading academics. The Arctic and sub-Arctic environment, climate, and biodiversity are changing in ways unprecedented in the long histories of the north, challenging traditional ways of life, well-being, and food security with legitimate concerns for the future of traditional Indigenous livelihoods. The book provides a clear and thorough overview of the potential problems caused by a warming climate on reindeer husbandry and how reindeer herders' knowledge should be brought to action. In particular, the predicted impacts of global warming on winter climate and the resilience of the reindeer herding communities are thoroughly discussed.